S09.3 The impact of screening on chlamydia transmission in australia -– a mathematical modelling study. (13th September 2015) - Hui, Ben; Hocking, J; Low, N; Regan, David
Abstract : Background: Repeat chlamydia infection following treatment is common among young people and is associated with increased risk of pelvic inflammatory disease. Retesting and providing treatment to infected partners can reduce the reinfection rate. Both strategies have their own merits and limitations. Here we present a comparison of the impact of these two strategies on population prevalence through the use of modelling. Methods: An individual-based model was developed to represent the transmission of chlamydia in a heterosexual population. A proportion of the modelled population is tested for chlamydia and treated annually under the testing coverage achieved in ACCEPt. We estimate the additional reduction in chlamydia prevalence achieved by retesting individuals who were infected with chlamydia and compare with the estimated reduction achieved by treating the partners of infected individuals. Results: Preliminary results suggest that retesting at the rate achieved in ACCEPt would yield an additional 0.7% to 1.0% reduction in chlamydia prevalence. This reduction is greater than would be achieved by treating 10% of infected partners of index cases alone, which only yields an additional 0.5% to 0.8% reduction in chlamydia prevalence. If 10% of infected partners are treated in addition to retesting, the model predicts a further 0.6% to 0.7% reduction in chlamydia prevalence. Conclusion: Both retesting and partner treatment can result in reductions in chlamydia prevalence in the population. Assuming that the retesting rate achieved in ACCEPt can be extended to the general Australian heterosexual population, this strategy should result in a greater reduction in prevalence than treating 10% of infected partners. More substantial reductions can be achieved by combining both strategies. Disclosure of interest statement: The Kirby Institute is funded by the Australian Government Department of Health and Ageing and is affiliated with the Faculty of Medicine, University of New South Wales. The views expressed in this publication do not necessarily represent the position of the Australian Government.